A BRIEF REVIEW OF TREATMENT MODALITIES FOR NON-MELANOMA SKIN CANCER - SHAH, HARSHIT (Asian Journal of Pharmaceutical and Clinical Research, 2021)
NMSC (Non-melanoma skin cancer) is the most commonly occurring malignancy in Caucasians. Out of all diagnosed NMSC cases, 95% of the cases are of basal cell carcinoma and squamous cell carcinoma. The therapeutic approaches to cure or ultimately rescue the skin area affected by NMSC include surgical methods, photodynamic therapy, radiation therapy, immunotherapy, and chemotherapy. This article aims to provide a brief overview of the preliminary mechanism of action, clinical studies, advantages, and disadvantages of currently available treatment modalities.